2007
DOI: 10.1007/s10620-006-9266-2
|View full text |Cite
|
Sign up to set email alerts
|

Intragastric Nitroglycerin at a Vasodilatory Dose Attenuates Acidified Aspirin-Induced Gastric Mucosal Injury

Abstract: Clinical studies reveal that aspirin intake to prevent myocardial and cerebral ischemia is associated with a significant increase in upper gastrointestinal hemorrhage requiring hospitalization and that nitroglycerin or long-acting nitrates significantly lower this risk. Nitroglycerin can increase gastric blood flow and slow gastric emptying. We hypothesized that both features contribute to its gastroprotective property. Fasted anesthetized rats (Study 1) and conscious mice (Studies 2 to 4) received intragastri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2007
2007
2008
2008

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 34 publications
(62 reference statements)
1
7
0
Order By: Relevance
“…Indeed, in a vasodilatory dose, i.g. nitroglycerin protects against acidified aspirin-induced gastric mucosal injury in mice [88]. One recent study demonstrated that aspirin enhance the recurrence of gastric ulcer induced by acetic acid [89], suggesting that the acetic acid gastric ulcer model is suitable for assessing the effect of nitroglycerin on the enhancement of ulcer recurrence by aspirin.…”
Section: Nitroglycerin and Aspirin-induced Gastric Injurymentioning
confidence: 99%
“…Indeed, in a vasodilatory dose, i.g. nitroglycerin protects against acidified aspirin-induced gastric mucosal injury in mice [88]. One recent study demonstrated that aspirin enhance the recurrence of gastric ulcer induced by acetic acid [89], suggesting that the acetic acid gastric ulcer model is suitable for assessing the effect of nitroglycerin on the enhancement of ulcer recurrence by aspirin.…”
Section: Nitroglycerin and Aspirin-induced Gastric Injurymentioning
confidence: 99%
“…This suggests that calibration of laser Doppler flowmeter in absolute units of blood flow may not be necessary inasmuch as significant hypotheses can be tested by determining relative or directional changes in blood flow. The use of normalized laser Doppler flowmetry values is an acceptable way of handling the data and has yielded meaningful conclusions in a number of physiological and pathophysiological studies in the gut [6,7,14,15,[30][31][32][33] and adipose tissue [34,35]. The laser Doppler flowmetry method can demonstrate the instantaneous onset of changes (increase or decrease) in the tissue under study.…”
Section: Assessment Of Adipose Tissue Blood Flow By Laser Doppler Flomentioning
confidence: 99%
“…The number of mucosal lesions was counted. The length of each lesion was measured by a caliper and summed to give the total length of mucosal lesions for each stomach [13,14].…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study we reported that intragastric nitroglycerin (5 mg/kg) increased gastric blood flow [14]. The intragastric gavage cannula for the mice was prepared by cutting the sharp tip of an 18-gauge Cathlon IV needle (Critikon, Tampa, FL).…”
Section: Study 1: Effect Of Intragastric Nitroglycerin (Vasodilatory mentioning
confidence: 99%
See 1 more Smart Citation